PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PROBLEM BASED LEARNING DENGAN MODEL PENGEMBANGAN ADDIE PADA MATERI HADITS DI MAN 2 MODEL MEDAN: Pembelajaran Pendidikan Agama Islam Berbasis Problem Based Learning Dengan Model Pengembangan ADDIE Pada Materi Hadis di MAN 2 Model Medan - Ahmad Fadil Dzaky; Lubis, Sakban (STAI Ma'had Aly Al-Hikam Malang, 2025)
The purpose of this study is to determine the contribution of Islamic education (PAI) learning based on PBL with the ADDIE development model. The research method is a descriptive qualitative method implemented at MAN 2 Model Medan. The steps in the learning process use PAI learning based on Problem-Based Learning (PBL) with the ADDIE development model. Data collection through student questionnaires about PBL and ADDIE learning syntax (analysis, design, development, implementation, and evaluation). The results of the student questionnaire showed that there was a relationship between PBL and ADDIE before the learning process, totaling 16 students, and after the learning process, totaling 19 students. The average student questionnaire before PBL was 64.3, and ADDIE was 67.8. The average student questionnaire after PBL was 66.0, and ADDIE was 72.7. N-Gain 0.6 is classified as moderate, indicating the effectiveness of learning in improving student learning outcomes, and the learning program has contributed to student understanding